PEDAGOGICAL ANALYSIS OF THE ASSESSMENT AND MONITORING PROCESSES OF PHYSICAL EDUCATION IN SECONDARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2026)
This article analyzes the issues of monitoring and assessing physical education in general education schools of the Republic of Uzbekistan. Since gaining independence, a number of state programs, decrees, and resolutions have been adopted to improve physical education, increase children’s physical activity, and promote a healthy lifestyle. The study involved a systematic monitoring of the schools’ material and technical base, teachers’ professional training, and students’ physical fitness indicators. The necessity of improving educational methodologies based on the diverse physical activities of children and their individual preferences is also emphasized. The article outlines directions for the effective organization of the physical education system in schools, the introduction of innovative pedagogical technologies, and the promotion of a healthy lifestyle, based on the results of scientific research and pedagogical experience.